A Swiss database and biobank to better understand and manage congenital lung anomalies (Swiss Medical Weekly, 2019)
Congenital lung anomalies are a group of rare malformations, often diagnosed during the prenatal period. Guidelines on how to manage these patients are currently under debate, especially with regard to prophylactic surgery in asymptomatic patients, or how to proceed with conservative follow-up. Currently, there is no clear consensus on management strategies. A Swiss congenital lung anomaly national database and biobank was created in 2016 to enable data recording and collection of surgical lung samples in order to help define the most appropriate management strategies. This national observational cohort study represents an important step towards a better understanding of the pathophysiology and clinical course of the diseases included under congenital lung anomalies, especially in the context of a small country like Switzerland.